2017
DOI: 10.1016/j.virusres.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of canine parvovirus and canine enteric coronavirus in diarrheic dogs on the island of St. Kitts: First report from the Caribbean region

Abstract: Although canine parvovirus (CPV) and canine enteric coronavirus (CCoV) are important enteric pathogens of dogs and have been studied extensively in different parts of the world, there are no reports on these viruses from the Caribbean region. During 2015-2016, a total of 104 diarrheic fecal samples were collected from puppies and adult dogs, with or without hemorrhagic gastroenteritis, on the Caribbean island of St. Kitts (KNA). By PCR, 25 (24%, n=104) samples tested positive for CPV. Based on analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
10
1
3
Order By: Relevance
“…Alphacoronavirus 1 is a major viral agent that causes gastrointestinal symptoms in dogs and cats. The detection frequency of CCoV in ill puppies in this study was low (27%) compared with that in other studies, with 65.1% of the samples positive for CCoV (Ntafis et al, 2013); some studies have shown low positive results of 4.8% (Navarro et al, 2017) for single infections, while other studies reported a prevalence of 20.3% for CCoV (Alves et al, 2018) and 18% for CPV in dogs (Wang et al, 2016). Infections with more than one virus are infrequent, and different studies have shown that the coinfection percentage varies between 20% (Soma et al, 2011) and 40% (Costa et al, 2014).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Alphacoronavirus 1 is a major viral agent that causes gastrointestinal symptoms in dogs and cats. The detection frequency of CCoV in ill puppies in this study was low (27%) compared with that in other studies, with 65.1% of the samples positive for CCoV (Ntafis et al, 2013); some studies have shown low positive results of 4.8% (Navarro et al, 2017) for single infections, while other studies reported a prevalence of 20.3% for CCoV (Alves et al, 2018) and 18% for CPV in dogs (Wang et al, 2016). Infections with more than one virus are infrequent, and different studies have shown that the coinfection percentage varies between 20% (Soma et al, 2011) and 40% (Costa et al, 2014).…”
Section: Discussioncontrasting
confidence: 85%
“…Two genotypes of CCoV are known, CCoV-I and CCoV-II, with type II divided into the subtypes CCoV-IIa (classical strains) and CCoV-IIb (TGEV-like strains), with a putative recombination between CCoV-II and TGEV strains (Decaro et al, 2010(Decaro et al, , 2009. In addition, one unique subtype has emerged in the past decade and belongs to CCoV-IIa; this subtype is considered pantropic as it can cause enteric and systemic signs, reported in Belgium, Brazil, France, Greece, Hungary, Ireland, Italy, Romania and the Caribbean island of St. Kitts (De Barros et al, 2018;Decaro et al, 2010;Navarro et al, 2017;Ntafis et al, 2013;Pinto et al, 2014;Soma et al, 2011;Zicola et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CPV2a is still circulating in domestic dogs in South America and predominant in Peru (21), Colombia (22), and recently an increase in the number of cases of this strain has been reported in Uruguay (25). The most recent reports from Latin America demonstrate the presence of the new CPV2a in Ecuador (28), Columbia (22), Brazil (7), and the Caribbean (29).…”
Section: Resultsmentioning
confidence: 99%
“…It spread briskly across Europe [19,20], America [17,21], Asia [22,23] and Australia [24]. Field studies showed that CPV-2c is becoming the predominant variant affecting the dog population worldwide [25][26][27]. The major antigenic difference between CPV-2 variants is a key amino acid at residue 426 in epitope A of the Viral Protein 2 (VP2).…”
Section: Ofmentioning
confidence: 99%